2001
DOI: 10.1038/88115
|View full text |Cite
|
Sign up to set email alerts
|

The HIV-1 DNA flap stimulates HIV vector-mediated cell transduction in the brain

Abstract: During HIV-1 reverse transcription, central initiation of the plus-strand DNA at the central polypurine tract (cPPT) and central termination at the central termination sequence (CTS) lead to the formation of a three-stranded DNA structure: the HIV-1 central DNA flap. We recently reported that the DNA flap acts as a cis-active determinant of HIV-1 genome nuclear import. Commonly employed HIV-1-derived vectors (HR vectors) lack the central DNA flap. Here we report that the insertion of this DNA flap sequence int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
133
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(141 citation statements)
references
References 16 publications
5
133
0
Order By: Relevance
“…22,29,30 Furthermore, cppt also increases levels of transgene via a poorly understood mechanism. Sakuma et al, 31 however, demonstrated that addition of the 282 bp fragment of the HIV-1 cppt resulted in impaired integration and a significant reduction in transduction.…”
Section: Discussionmentioning
confidence: 99%
“…22,29,30 Furthermore, cppt also increases levels of transgene via a poorly understood mechanism. Sakuma et al, 31 however, demonstrated that addition of the 282 bp fragment of the HIV-1 cppt resulted in impaired integration and a significant reduction in transduction.…”
Section: Discussionmentioning
confidence: 99%
“…Stocks of viral particles were prepared as described previously (Naldini et al, 1996;Zennou et al, 2001) by transient cotransfection of HEK 293T cells with the p8.91 encapsidation plasmid (Zufferey et al, 1997), the pHCMV-G (vesicular stomatitis virus pseudotype) envelope plasmid and the pFlap vectors described above (Lv-shSCLIP, Lv-shCtrl, Lv-SCLIP, or Lv-GFP). Briefly, the supernatants were collected 48 h after transfection, treated with DNase (Roche) before ultracentrifugation, and then resuspended in PBS, aliquoted, and stored at Ϫ80°C until use.…”
Section: Recombinant Lentiviral Productionmentioning
confidence: 99%
“…The most striking recent claim is for a specific role in facilitation of HIV-1 nuclear import in both dividing and non-dividing cells [104,123]. It is possible, but unproven, that the central single-strand discontinuity enhances steric fit in the nuclear pore, by optimizing folding of the double-stranded DNA [103,104].…”
Section: Mechanisms Of Lentiviral Nuclear Import: Central Dna Flaps Amentioning
confidence: 99%
“…In the model based on these data, cPPT-minus viruses become blocked at the step of nuclear translocation [104]. Studies with replicating virus and replicationdefective HIV-1 vectors have lent support to the hypothesis [104,123,124]. However, recent reassessments have challenged this functional assignment [125,126].…”
Section: Mechanisms Of Lentiviral Nuclear Import: Central Dna Flaps Amentioning
confidence: 99%